Uptake and safety of community‐based "screen‐and‐treat" with thermal ablation preventive therapy for cervical cancer prevention in rural Lilongwe, Malawi. Issue 2 (23rd March 2021) - Chinula, Lameck; Topazian, Hillary M.; Mapanje, Clement; Varela, Amanda; Chapola, John; Limarzi, Laura; Stanley, Christopher; Hosseinipour, Mina; Gopal, Satish; Tang, Jennifer H.
Abstract: Malawi has the highest invasive cervical cancer (ICC) mortality rate worldwide, and ICC is the leading cause of cancer death among women. In 2004, Malawi adopted visual inspection with acetic acid (VIA) and ablative treatment with cryotherapy. However, screening coverage has remained low (<30%) and few women (<50%) who require ablative treatment receive it. Additional barriers include long distances to health facilities and challenges with maintaining gas supplies. Thermal ablation is a safe and effective alternative to cryotherapy. We assessed the safety and uptake of community‐based ICC screening with VIA and same‐day treatment using a handheld thermocoagulator (HTU) in rural Malawi. We held educational talks alongside community leaders and conducted VIA screening in nonclinic community settings to nonpregnant women aged 25 to 49 years without history of hysterectomy or genital cancer/precancer. Eligible women received same‐day thermal ablation and HIV testing/counseling. We collected cervical biopsies before treatment and followed up women at Weeks 6 and 12, with repeat biopsy at Week 12. Between July and August 2017, 408 (88%) of 463 eligible women underwent VIA. Overall, 7% (n = 30) of women had a positive VIA, of whom 93% (n = 28) underwent same‐day thermal ablation. Among the 30 VIA‐positive women, 5 had cervical intraepithelial neoplasia (CIN) 1, 4 had CIN 2/3 and 21 had benign histologic findings. Abnormal vaginal discharge (60%) and light vaginal bleeding (52%) were the most reported adverse events. There was high uptake of the community‐based ICC screening in the study population and treatment was safe in this setting. Similar strategies that minimize false‐positive results are urgently needed in Malawi. Abstract : What's new? Malawi has the world's highest incidence and mortality rates of invasive cervical cancer. In 2004, the country adopted a screen‐and‐treat program using visual inspection with acetic acid (VIA) and ablative treatment with cryotherapy. However, women's participation remained low, and the high cost of cryotherapy means that not all who need ablative treatment can receive it. Here, the authors test the safety and uptake of a screening program with same‐day thermal ablation in a community setting. In rural Lilongwe, Malawi, 88% of eligible women participated in cervical screening, and thermal ablation was shown to be safe in a non‐clinical setting.